Potentially pathogenic Acanthamoeba genotype T4 isolated from dental units and emergency combination showers - Castro Artavia, Esteban (2017)
Background: Acanthamoeba is the genus of free-living amoebae that is most frequently isolated in nature. To date, 20 Acanthamoeba genotypes have been described. Genotype T4 is responsible for approximately 90% of encephalitis and keratitis cases. Due to the ubiquitous presence of amoebae, isolation from environmental sources is not uncommon; to determine the clinical importance of an isolation, it is necessary to have evidence of the pathogenic potential of amoebae. Objective: The aim of this study was to physiologically characterise 8 Acanthamoeba T4 isolates obtained from dental units and emergency combination showers and to determine their pathogenic potential by employing different laboratory techniques. Methods: Eight axenic cultures of Acanthamoeba genotype T4 were used in pathogenic potential assays. Osmotolerance, thermotolerance, determination and characterisation of extracellular proteases and evaluation of cytopathic effects in MDCK cells were performed. Findings: All of the isolates were osmotolerant, thermotolerant and had serine proteases from 44-122 kDa. Two isolates had cytopathic effects on the MDCK cell monolayer. Main conclusion: The presence of Acanthamoeba T4 with pathogenic potential in areas such as those tested in this study reaffirms the need for adequate cleaning and maintenance protocols to reduce the possibility of infection with free-living amoebae